Aspek Yuridis dan Implementasi Manajemen Benda Sitaan Negara di RUPBASAN - Hutagalung, Gabryela Stevy (JIMLY LEGAL YUSTISIA JOURNAL, 2024)
The State Seized Goods Storage House (RUPBASAN) plays a crucial role in managing confiscated and forfeited assets. However, various issues arise regarding storage systems, management, and auctions that often do not comply with applicable legal provisions. This study examines the juridical aspects of confiscated goods management in RUPBASAN through an analysis of legislation and a review of legal journal literature. The findings indicate weaknesses in regulations related to supervision mechanisms, storage standards, and auction procedures for seized and forfeited assets. Therefore, regulatory harmonization and policy improvements are needed to ensure more effective, transparent, and accountable asset management in RUPBASAN.